Kedudukan Hukum dalam Mewujudkan Keadilan dan Kesejahteraan di Indonesia - Nasir, Melisa; Khoiriyah, Elmi; Pamungkas, Bagus Priyono; Hardianti, Inas; Zildjianda, Raesitha (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of law itself includes three values, namely, the value of justice, expediency, and legal certainty. But unfortunately, actual practice in the world of law often does not emphasize all values ​​and tends to forget one importance. Therefore, an understanding has arisen that justice is the most critical value in direction. The purpose of this paper is to find out the concept of justice in the rule of law in Indonesia and describe the position of law that can create an ideal legal system in Indonesia so that the context of the welfare State Can Be Realized. The research method used is a descriptive analysis which leads to normative juridical research, namely research conducted by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials, and tertiary legal materials. The role of the law in realizing people's welfare must be seen in the fabric of the law in the moral integrity of law enforcement officials.